Pencatatan Sederhana untuk Meningkatkan Efisiensi dan Efektifitas Pengelolaan Keuangan pada UMKM Jawara Bojongsari Depok - Indawati, Indawati; Anggraini, Anggun; Ruhiyat, Endang (Jurnal PKM Manajemen Bisnis, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in driving the local economy, yet many still struggle with effective financial management due to a lack of basic bookkeeping skills. This community service activity (PKM), titled "Simple Bookkeeping to Improve the Efficiency and Effectiveness of Financial Management for UMKM Jawara Bojongsari", aimed to address these challenges by equipping MSME actors with practical knowledge of simple financial recording methods. The program was conducted in April 2025 in Bojongsari Subdistrict, Depok City, and involved 15 lecturers from Universitas Pamulang as facilitators. A total of 25 MSME participants from the Jawara (Jaringan Wirausaha) Bojongsari network took part in the training. The implementation methods included material presentations, hands-on practice, group discussions, and Q&A sessions. As a result, participants gained a better understanding of financial recording practices such as income and expense tracking, ledger preparation, and basic financial planning. The activity significantly increased participants' financial awareness and confidence in managing their businesses. This PKM program demonstrated that structured and practical financial education can contribute positively to improving the financial literacy and operational efficiency of local MSMEs.